COOPERATIVE LEARNING METHOD IN SENIOR HIGH SCHOOL ENGLISH CLASSES: STUDENTS’ AND TEACHERS’ PERCEPTIONS - Alfin Andya Ade Kriesna (ELTR Journal, 2023)
There are many methods in the English education world. One of them is a cooperative learning method. This paper aims to find the students’ and teachers’ perceptions of the cooperative learning method in Senior High School classes. This study used qualitative study. All data were analyzed qualitatively. The instruments used were questionnaires and semi-structured interviews. The participants were 45 students of one of the Senior High School English classes and 2 English teachers in Salatiga. Based on the findings, the cooperative learning method could potentially become an effective method for students. Based on the result, the students felt happy with this method. Moreover, this method could develop students’ teamwork skills. In teachers' perceptions, they taught through group work in this method could enhance students’ knowledge of the material. However, both students and teachers argued that this method could be less effective when there were uncooperative teammates in the group.